Power your tribe : create resilient teams in turbulent times - Comaford-Lynch, Christine (McGraw-Hill Education, 2018)
Filled with case studies and all-too-familiar examples, this groundbreaking book will enable you to release resistance to change, build more emotionally agile teams, and mobilize the entire organization quickly and efficiently toward a clear and common goal. --